Sistem Pendukung Pengambilan Keputusan Penerimaan Beras Untuk Keluarga Miskin (Raskin) Di Kelurahan Sondakan Kecamatan Laweyan Kota Surakarta - Kusmiati, Wawan Laksito YS, Tri Irawati (STMIK Sinar Nusantara, 2012)
The purpose of submitting this research paper as a partial fulfillment of the requirements for getting bachelor degree on the STMIK Sinar Nusantara, also aims to facilitate the process of determing the recipients raskin in the Sondakan. The method of collecting data used by the author in the preparation of this paper is an interview with the KASI of community development and feasibility assessment methods related to the recipient rice requirements raskin recipient. In the “Decision Support System Acceptance Raskin” author provides a range calculation process based on the economic circumstances, the admissions raskin process based on the range value. the results of this study stated that to get